Research update on the effects of probiotic supplementation during pregnancy on pregnancy complications: a systematic literature review - Jing YANG; Xiaochuan WANG; Borui LIU; Xiaoyan ZHANG; Xiaoyu GAO; Jiajin HU (Zhongguo gonggong weisheng)
A growing body of research suggests a correlation between probiotic supplementation during pregnancy and the prevention and treatment of pregnancy complications. As modulators of gut microbiota, probiotics possess anti-inflammatory and immunomodulatory properties, potentially offering benefits in preventing pregnancy complications and improving clinical symptoms. This review aims to summarize the potential effects of probiotic supplementation during pregnancy on common pregnancy complications, including gestational diabetes mellitus, preeclampsia, intrahepatic cholestasis of pregnancy, premature birth and spontaneous abortion, due to the current limitations in clinical research on probiotics and the heterogeneity of existing findings. This review provides a reference for the clinical application of probiotic supplements in the prevention and treatment of pregnancy complications.